Effect of Defoamer of Botanical Insecticide Nanoemulsion Paramentandiol to Control Spodoptera frugiperda (Lepidoptera: Noctuidae) - Fadhlurrahman, Rayhan; Lina, Eka Candra; Nelly, Novri (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2026)
Formulating a stable para-menthane-3,8-diol (PMD) nanoemulsion requires a balanced ratio of active ingredients and surfactants. Increasing the active ingredient may improve efficacy but can reduce stability, while excessive surfactant levels may cause unwanted foaming during application. This study evaluates the use of a defoamer to improve nanoparticle stability and enhance the biological activity of the formulations against Spodoptera frugiperda. The research was conducted in two stages: (1) characterization of particle stability using the DLS method and (2) evaluation of insecticidal activity through the leaf-dip bioassay. Data were analyzed using ANOVA followed by the LSD test; LC50 and LC95 values were determined via Probit analysis using POLO PLUS. The addition of a defoamer significantly improved the physicochemical properties and performance of the PMD nanoemulsion. The formulation achieved a refined particle size of 202.2 nm and a PDI of 0.20, both within acceptable nanoparticle standards. At a concentration of 0.25%, the defoamer-enhanced formulation demonstrated superior biological efficacy, including a 0.07% increase in LC95 efficiency and 3.14% growth inhibition. The treatment reduced pupal formation and adult emergence by 8% and altered the sex ratio. The addition of a defoamer improves the physical properties of the nanoemulsion and its biological efficacy against Spodoptera frugiperda.